Imaging Brain Oxygenation with MRI Using Blood Oxygenation Approaches: Methods, Validation, and Clinical Applications - Christen, T.; Bolar, D.S.; Zaharchuk, G. (American Journal of Neuroradiology, 2013)
SUMMARY: In many pathophysiologic situations, including brain neoplasms, neurodegenerative disease, and chronic and acute ischemia, an imbalance exists between oxygen tissue consumption and delivery. Furthermore, oxygenation changes following a stress challenge, such as with carbogen gas or acetazolamide, can yield information about cerebrovascular reactivity. The unique sensitivity of the BOLD effect to the presence of deoxyhemoglobin has led to its widespread use in the field of cognitive neurosciences. However, the high spatial and temporal resolution afforded by BOLD imaging does not need to be limited to the study of healthy brains. While the complex relationship between the MR imaging signal and tissue oxygenation hinders a direct approach, many different methods have been developed during the past decade to obtain specific oxygenation measurements. These include qBOLD, phase- and susceptibility-based imaging, and intravascular T2-based approaches. The aim of this review is to give an overview of the theoretic basis of these methods as well as their application to measure oxygenation in both healthy subjects and those with disease. BOLDblood oxygen level–dependentCMRO2cerebral metabolic rate of oxygen consumptionOEFoxygen-extraction fractionpO2partial pressure of oxygenqBOLDquantitative BOLDQUIXOTICQUantitative Imaging of eXtraction of Oxygen and TIssue ConsumptionSaO2arterial oxygen saturationSO2blood oxygen saturationSvO2venous oxygen saturationTRUSTT2-relaxation under spin-tagging